Workshop Project Based Learning: Cara Memulai Usaha yang Cerdas - Diah Pranitasari; Doddi Prastuti; Pristina Hermastuti; Kus Tri Andyarini; Enung Siti Saodah; Kus Tri Dianavera (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta (BPJP - STEI), 2022)
Sekolah Menengah Kejuruan (SMK) aims to produce graduates who are ready to enter independent employment as entrepreneurs. With the average age of students still in a productive period to receive science and technology, including entrepreneurship, SMK is very important in preparing graduates who are ready to enter into entrepreneurship. For this reason, entrepreneurial characteristics in vocational schools need to be conditioned either through intracurricular, co-curricular and extracurricular activities. To fulfill the above, the Community Service Team conducted a workshop in the form of a webinar to students of SMK Paramitha Jakarta, with the aim of providing explanations and directions to students about the positive benefits of starting a business at a young age, providing explanations and directions for students to be able to start a business. intelligently and appropriately, and directing students so that they can market their business results appropriately. Through this activity, students are expected to be able to understand the positive benefits of starting a business at a young age. In addition, students are also expected to be able to start a business smartly and appropriately and have the ability to market their business results appropriately.